2019
DOI: 10.24198/jit.v19i1.21470
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Rumpun Domba Terhadap Lama Waktu Makan dan Lama Ruminasi

Abstract: Pengaruh Rumpun Domba Terhadap Lama Waktu Makan dan Lama RuminasiEfek Suku Domba terhadap Waktu Makan dan Merenung Arsya Subhan 1, a , Kurnia A. Kamil 2 , Denie Heriyadi 21 Mahasiswa Program Studi Pascasarjana Fakultas Peternakan Universitas Padjadjaran2 Dosen Program Studi Pascasarjana Fakultas Peternakan Universitas Padjadjarana arsya4u@gmail.com  ABSTRAKPenelitian ini bertujuan untuk mengetahui perbedaan lama makan dan lama ruminasi dari tiga rumpun domba yaitu Domba Garut, Domba Priangan, dan Domba Lokal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…Based on these data it can be seen that body length, foreleg length, hip width, hip height and crotch width greatly affect body weight in rams. This is not following [6] which states that body length, chest circumference and hip height are morphometric characteristics that have a very close relationship in determining the body weight of sheep. In this study, it was found that chest circumference did not affect body weight in Waringin rams, but other morphometric factors affected body weight which included body length, hip width and crotch width.…”
Section: Analysis Of Datamentioning
confidence: 94%
See 1 more Smart Citation
“…Based on these data it can be seen that body length, foreleg length, hip width, hip height and crotch width greatly affect body weight in rams. This is not following [6] which states that body length, chest circumference and hip height are morphometric characteristics that have a very close relationship in determining the body weight of sheep. In this study, it was found that chest circumference did not affect body weight in Waringin rams, but other morphometric factors affected body weight which included body length, hip width and crotch width.…”
Section: Analysis Of Datamentioning
confidence: 94%
“…Based on these data it is known that the morphometric parts that affect body weight are body length, skull length, chest circumference, hip height, tail length, tail width and crotch width. This is following [6] which states that body length, chest circumference and hip height are morphometric characteristics that have a very close relationship in determining the body weight of sheep. in the Stabat sub-district has a higher body weight than the thin-tailed and fat-tailed sheep, this is due to genetic and environmental factors in the Stabat sub-district.…”
Section: Analysis Of Datamentioning
confidence: 99%
“…Chest circumference was measured by circling the chest cavity through os scapula using a measuring tape in cm. Then the height at withers is the highest distance from the shoulder to the ground, it was measured using a measuring stick in cm (Heriyadi and Mayasari, 2006).…”
Section: Body Measurementsmentioning
confidence: 99%
“…Domba menutupi kebutuhan nutrisi dan energinya dengan merumput di padang rumput. Peternakan domba berbasis padang rumput telah dipraktikkan di negara-negara dengan sistem pembiakan yang maju seperti Australia, Amerika, dan Selandia Baru [1] Peningkatan jumlah hewan peliharaan domba sangat dibutuhkan untuk memenuhi kebutuhan masyarakat setiap hari [6]. Produktivitas peternakan sangat tinggi itu dipengaruhi oleh dua faktor utama, yang disebut genetik dan lingkungan.…”
Section: Pendahuluanunclassified